A Multi-center Study on Bronchiectasis in Active Tuberculosis (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Bronchiectasis may be found in pulmonary tuberculosis (PTB) as a feature of a chronic inflammatory process and is usually considered chronic traction bronchiectasis associated with healed scars. However, bronchiectasis can occasionally be seen in active TB. Aim of the study: To evaluate the presence of bronchiectasis in chest radiographs as a feature of active TB. Methods: A total of 92 patients with active TB who had diagnostic chest X-rays were included in the study. Among them, 20 patients had active TB, as the gene expert was positive. The X-rays were reviewed, focusing on bronchiectasis within consolidations or inflammation. Cases with bronchiectasis beyond the consolidation or inflammatory change were excluded from the study to exclude pre-existing traction bronchiectasis. 3 out of the 20 patients with bronchiectasis had a previous history of TB and were excluded from the study. Results: In 17 (18.48%) of the 92 patients, bronchiectasis was present within consolidations or inflammation on chest radiographs. Conclusion: Bronchiectasis can be seen within active inflammation in one-fourth of active TB on chest x-rays.BJRI, 2024; VOL. 32(2): 107-111